Songke Fabric in Libo, Wela Kaweng and Su'i Motif from Perak Village, Manggarai Regency, East Nusa Tenggara, in Study of Visual Aesthetics of Meaning and Function - Mariani Irma Yanti Pantur; Ika Ismurdiyahwati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2023)
Songke fabrics with libo, wela kaweng and su'I motifs are a type of Indonesian textile work. Songke cloth with libo, wela kaweng and su'I motifs is a textile work from Perak village, Manggarai Regency, East Nusa Tenggara. This research takes the topic of the libo, wela kaweng and su’I motifs on songke cloth in Perak village, Manggarai Regency, because these motifs are superior motifs that are often produced and a cultural heritage that has its own meaning and function. Therefore, this study aims to determine the visual aesthetic meaning and function of songke cloth in libo, wela kaweng and su'I motifs on songke cloth. The data sources in this study are the figures of songke cloth craftsmen, the village head, and cultural observers. This type of research uses descriptive qualitative with an explanation through the data obtained from data collection using the method of observation, documentation, and direct interviews. The results of this study show that the libo motif means the relationship between humans and the natural surroundings where in everyday life humans always need water to sustain life. The wela kaweng motif means a plant that can be used as medicine to heal and treat livestock wounds in ancient times and the su’I motifs means as a bridge that separates the customs between the tribes in the Silver Village. Songke fabrics with libo, wela kaweng and su'I motifs are used by the Manggarai community in attending traditional ceremonies such as engagements, weddings, penti (year-end thanks giving or every harvest) and funerals.